Out of the public eye: The International Labour Organisation in the media - Frank Nullmeier (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2014)
Politics takes place in public communication and is part of public communication. Today, public communication is substantially determined by the media. This is also the case for the field of global social policy. The following study addresses the question of how global social policy and, in particular, the International Labour Organization (ILO) as the key player in global social policy, is discussed in the media. Are global social policy and the ILO visible at all in the media? To what extent is the organisation visible? How do the media report about the ILO and on what exactly does media coverage of the ILO focus? – – Politik vollzieht sich in öffentlicher Kommunikation. Und diese wird wesentlich durch mediale Angebote bestimmt. Das trifft auch auf die globale Sozialpolitik zu. Die vorliegende Studie beschäftigt sich mit der Frage, wie globale Sozialpolitik - und insbesondere die Internationale Arbeitsorganisation (ILO) als deren zentraler Akteur - in den Medien dargestellt werden. Wie hoch ist die mediale Aufmerksamkeit für das Thema globale Sozialpolitik? Zu welchen Anlässen wird die Presse auf die ILO aufmerksam? Wie sichtbar ist die ILO als Organisation, als politischer Akteur und als Informationsgeber? Wie berichten die Medien über die ILO und welches Bild dieser internationalen Organisation entsteht dadurch?
Keywords: 300; Internationale Organisation; Sozialpolitik; Medienwirkung; Öffentliche Meinung